Sollbruchstellen des deutschen, europäischen und internationalen Flüchtlingsrechts - Thym, Daniel (De Gruyter, 2019)
Refugee law has recently become the focus of public debate. It various topics such as the failure to close the German border during the refugee crisis, cooperation with third countries such as Turkey or Libya, national housing standards, a reformed Dublin system and much more. Common to all these subject areas is that they are political Combine fundamental questions with legal details and one Demand an overall view of German, European and international legal rules. This complex mixed situation makes it difficult to determine the location asks about the structural problems of refugee law and thus the proverbial forest for the trees.
"The Weaknesses of German, European, and International Refugee Law" -- translation of title provided by publisher.
"Aktuelle und erweiterte Fassung des am 20. Februar 2019 vor der Juristischen Gesellschaft zu Berlin gehaltenen Vortrages: "Deutsches, europäisches und Internationales Flüchtlingsrecht: aus der Zeit gefallen?" --- title page.
Keywords: Refugees -- Legal status, laws, etc. -- Germany.; Refugees -- Legal status, laws, etc. -- European Union countries.; Refugees -- Legal status, laws, etc.; Law.; Refugees & political asylum.; LAW / Emigration & Immigration.; European Union countries; Germany; Electronic books.